Prevalence of breast cancer and its associated factors for recurrence in Hospital Tengku Ampuan Afzan from 2008 to 2012 - Mahno, Noor Ezmas; Muhammad Amjad, Nasser; Kasian, Junaini; Chik, Azhani (International Islamic University Malaysia, 2022)
INTRODUCTION: Breast cancer is the commonest malignancy in Malaysian women. Cancer recurrence commonly seen in the first 2 years can be detrimental. Thus, identifying its prognostic factors is important. MATERIALS AND METHODS: We have retrospectively analyzed 179 women with breast cancer based on 5 years single center database with minimum follow up of 2 years. The demographic and clinico-pathological characteristics were determined using descriptive statistics. Survival was calculated based on Kaplan-Meier method. Multivariate analysis by Cox proportional hazards was performed to evaluate the potential factors affecting breast cancer recurrence. RESULTS: Mean follow up was 42 months, with mean age 52 years and 60.9% presented in Stage II disease. Overall recurrence was 41.9% with local recurrence 2.1%, regional recurrence 12.3% and distant recurrence 27.4%. 50% of our patients developed recurrence at 25 months. On univariate analysis, time to first presentation was significantly correlated with recurrence. In multivariate analysis, the tumor size, lymph node positivity and lympho-vascular invasion were independently associated with recurrence. Discussion: To date, local studies on prognostic factors in breast cancer recurrence remained sparse. Based on this study, factors associated with breast cancer recurrence identified and coincides with the previous evidence. Furthermore, this would provide evidence to improve the survival for patients with breast cancer in local settings. CONCLUSION: Further studies also need to be done on the non-compliant patients with advanced disease at presentation to determine factors towards their perception of surgical care in breast oncology.